Analysis of the Effect of Harvest Area, Agricultural Credit, Labor, on Food Production (Rice and Corn) in North Sumatra - Nopiansyah Putra (IHSA Institute, 2022)
The title of this research is to analyze the influence width on farm, credit banking of agriculture sector and man power of agriculture sector in influencing of rice and maize product in North Sumatra. The data used is time series in the period of 1988-2007. The method used ordinary last square (OLS). The result of the research shows that the influence width on farm, credit banking of agriculture sector and man power of agriculture sector is influence which are positive to product domestic rice and maize and statistically significant at 5 % .